The Future of the Sectors and the Change of the Firms in the Post-pandemic Period - Keskin, Halit (TUBA-TURKISH ACAD SCIENCES, 2020)
The COVID-19 virus, spreading from Wuhan city of China to the world, envelops and changes the World. The COVID-19 virus emerged in China is a RNA-based virus like the SARS virus but unlike the SARS, COVID-19 has the possibility to transmit very quickly and easily. The SARS was taken under control very quickly and restrained to spread out of China. COVID-19, on the contrary, has spread all over the world and disrupted both social and economic dynamics. Convincing facts about the existence, emergence and spread of the virus require changes and transformations in the global economy, on macro, meso and micro bases. This situation makes it necessary to consider the transformation in the global economy and foreign trade and the adaptation to the new normal on a macro basis. When it comes to mezo base, focus should be on the rising and falling sectors due to COVID-19, and future plans for these sectors should be drawn. On a micro basis, the business plans of the companies should be rearranged together with their business models, new internal governance practices should be focused on, and opportunities to adapt to the new normal should be evaluated. In this study, these issues are discussed respectively.
Keywords: COVID-19; Corona Crisis; Organizational Practices; Pandemic; Resilience; Sector Transformation; Public, Environmental & Occupational Health; Social Issues; Social Sciences - Other Topics